ANALYSIS OF PARTNERSHIP DEVELOPMENT USING ARCHETYPE SYSTEM MODELING IN AN EFFORT TO INCREASE THE LEVERAGE OF TOUGH TEMPE UMKM BUSINESSES IN HUTAGODANG VILLAGE - Nasution, Dini Andriani; Harahap, Rahmat Daim; Nasution, Juliana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to identify the internal environment as strengths and weaknesses and the external environment as opportunities and threats and then formulate alternative strategies that can be implemented regarding the next Tempe SME partnership program. This study examines the leverage of each system archetype model in UMKM partnerships and also uses an internal matrix (IFE) and an external matrix (EFE). From the EFAS and IFAS data calculations above, it can be seen that the company's current position is in quadrant I coordinates (1,946 ; 1,395) namely the expansion (growth) quadrant, which is expected to be able to maintain and sustain the strategy and be able to penetrate the market and develop products. Based on the results of the model simulation process with the Casual Leverage Loop System, it is hoped that there will be several relationship structures between elements that influence each other in UMKM and partners, namely partners from large companies that have industrial scope both in the tofu-tempeh trade chain area and even the soybean import industry. Meanwhile, looking at the results of the partnership structure which was built from three sides, namely as follows: Business information perspective, business competency perspective and business access perspective. Keywords: Partnership, Archetype System, UMKM